4-Aminopyridinium 4-aminobenzenesulfonate 4-ammoniobenzenesulfonate monohydrate - Fun, Hoong-Kun (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(5)H(7)N(2) (+)·C(6)H(6)NO(3)S(−)·C(6)H(7)NO(3)S·H(2)O, contains one 4-ammoniobenzenesulfonate zwitterion ((+)H(3)NC(6)H(4)SO(3) (−)), one 4-aminobenzenesulfonate anion (H(2)NC(6)H(4)SO(3) (−)), one 4-aminopyridinium cation and two half-molecules of water, each lying on a twofold rotation axis. The various ions and molecules in the structure are linked through N—H⋯O, N—H⋯N and N—H⋯S hydrogen bonds and C—H—π interactions into a three-dimensional framework.